Salivary Cortisol, Salivary Alpha Amylase, and the Dental Anxiety Scale. - Sadi, Hana. (2017)
Abstract: Aim: The aim of this study was to investigate the correlation between dental anxiety (measured using Corah's Dental Anxiety Scale), salivary cortisol, and salivary alpha amylase levels. Furthermore, the aim was to look into individual differences such as age, race, gender, any existing pain, or traumatic dental experience and their effect on dental anxiety. Introduction: Dental anxiety has negative ramifications on people's quality of life and remains as a barrier for many people from seeking proper dental care. Dental anxiety is a form of psychological stress, and its effects are seen via activation of two pathways: First, the Hypothalamic-Pituitary-Adrenal axis (HPA), which causes the release of cortisol to all body fluids. Second, the autonomic nervous system (ANS); which causes the release of epinephrine and norepinephrine. Literature has shown that when the ANS gets activated, the level of salivary alpha amylase (sAA) increases in the saliva. The interest in sAA, as a biomarker of stress, has increased in bio-behavioral research, as it reflects the ANS activity and is non-invasive to obtain. Cortisol correlation with anxiety has been demonstrated in prior literature; however, to our knowledge its correlation with sAA has not been reported. Therefore, this study looked primarily at the effect of dental anxiety on salivary cortisol and sAA levels. Methods: This study followed a cross-sectional design and included a convenience sample of 46. Every patient was asked to complete the Dental Anxiety Scale, and a basic demographic/dental history questionnaire. A saliva sample, utilizing the method of passive drooling, was then collected in 2ml cryovials. Samples were analyzed for cortisol and sAA levels, which were the primary outcomes. Results: Significant associations were found between DAS scores and presence of pain and traumatic experience in women. No significant correlations were found between DAS, cortisol, and sAA levels for both genders. Conclusion: The level of dental anxiety is affected by presence of pain and a traumatic dental history, especially in females. Our study was the first to our knowledge to test the correlation between DAS and salivary alpha amylase, nevertheless, our results failed to show any correlation between DAS, cortisol, and sAA levels.; Thesis (M.S.)--Tufts University, 2012.; Submitted to the Dept. of Other.; Advisor: Morton Rosenberg.; Committee: Matthew Finkelman, Michael Thompson, and Daniel Oreadi.; Keyword: Dentistry.